Anatomical and morphological aspects of papillae, epithelium, muscles, and glands of rats’ tongue: Light, scanning, and transmission electron microscopic study - Davydova, Ludmila (Interv Med Appl Sci, 2017)
PURPOSE: The purpose of this paper is to describe the research results of the morphological structure of white laboratory rats’ tongue at the macro-, micro-, and ultrastructural levels by scanning, light, and transmission electron microscopy. RESULTS: Our results show that the tongue of these rats has a number of unique morphological features that are different from the tongue of other rodents consequently to allow identifying their species-specific features. CONCLUSIONS: Our findings have shown the features of the tongue structure of white laboratory rats at micro-, macro-, and ultrascopic levels. The data analysis revealed that mucous membrane of the tongue contains a large number of papillae, such as fungiform, filiform, foliate, vallate, and multifilamentary papillae. Each has a different shape, size, and location. The tongue’s morphological feature consists of three types of filiform papillae, well-developed foliate and multifilamentary papillae, as well as one large and similar smaller circumvallate papillae. The muscle of the tongue contains a large number of mitochondria of different shapes and sizes. However, we have received data for a complete picture of structure of this organ that will be useful in further experimental and morphological studies of the white laboratory rats.